The Existence of The Main Character's Crime in The Short Stories of Berenice and The Tell-Tale Heart by Edgar Allan Poe - Ai Nurelah; Erik Chandra Pertala; Siska Hestiana (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
This study examines the existence of crimes committed by the protagonists of Edgar Allan Poe's short stories "Berenice" and "The Tell-Tale Heart". This study aims to describe the crimes committed by the main character of both short stories. The data sources used are short stories, books, and website. In this study, we categorize the data into subchapters and analyze them. The authors use the theory of Maguire et al., 2012. Crime description. When analyzing research data using descriptive qualitative methods. According to research results, some of the acts included in the two short stories that fall under the category of crime are horrific.